Incidence of ectopic pregnancy at the "Enrique C. Sotomayor" gynecological-obstetric Hospital from 1985-1990. - JARAMILLO Q, ANGELA; Dáher Nader, Jorge Elías (Revista Universidad de Guayaquil, 1990)
396 patients were studied, from 1985 to 1990, grouping them according to age, marital status, socio-economic stratum, history of pregnancy, parity, cesarean section and abortions, weeks of gestation, location, provisional diagnosis at admission, symptoms, complications: upon admission, main primaries, secondary and form of completion. Percentages were obtained for performing laparotomy, culdocentesis, ultrasound, paracentesis, laparoscopy, ruptured and organized ectopic pregnancy, recurrence of ectopic pregnancy, prognosis, hypovolemic shock and IUD, in comparison with the total number of cases of ectopic pregnancy admitted in said period.